Financial Stability Issues in Emerging Market and Developing Economies - Financial Stability Board; International Monetary Fund; World Bank (World Bank, Washington, DC, 2017)
The focus of the paper is on five key financial stability issues in Emerging market and developing economies (EMDEs), which have been selected on the basis of their degree of materiality for a reasonably broad range of EMDEs; their implications for regulatory, supervisory or other financial sector policies; and the extent to which these issues are not already being addressed by other international work streams. The paper does not cover other financial stability issues that may also be relevant for EMDEs but are addressed in other G20/Financial Stability Board (FSB) work streams. Such issues include the management of sizeable and volatile capital flows; the design of policy measures to address the risks arising from systemically important financial institutions; the development of macro-prudential policy frameworks; the creation of effective resolution tools and regimes for financial institutions; strengthening the oversight and regulation of the shadow banking system; and reforming the functioning of over-the-counter derivatives and commodities markets. This paper focuses on five key financial stability issues in EMDEs: 1) application of international financial standards; 2) promoting cross-border supervisory cooperation; 3) expanding the regulatory and supervisory perimeter; 4) management of foreign exchange risks; and 5) developing domestic capital markets.